Pertumbuhan dan perkembangan anak gizi buruk masa lalu di Kabupaten Tanggamus Provinsi Lampung - Suhartono Suhartono; Drajat Boediman; Toto Castro (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2008)
Background: Undernutrition is one of factors that influences growth and development of children and causes lost generation. In Indonesia, 2.4 million of underfives suffered from undernutrition and 7 millions of them suffered from protein energy malnutrition. In Tanggamus Regency, 46% of children suffered from protein energy malnutrition and 81 cases suffered from undernutrition.Objective: To identify the relationship between children’s previous undernutrition and their recent growth and development.Method: The study was observational with cross sectional design. Subjects were all undernutrition cases nursed in Regional Public Hospital of Pringsewu Tanggamus from 1999–2001. Antropometric measurement was done to children’s weight and height. The anthropometric indicators were weight for age z-score (waz), height for age z-score (haz), and weight for height z-score (whz). Raw motoric development was measured using Denver test. Data collected using questionnaire were child internal factors and external factors of family’s characteristics and health service. One variable analysis was done descriptively, while t-test was used to know the relationship between children’s previous undernutrition and their recent growth development.Results: There was relationship between previous undernutrition of children and their recent growth (p<0,05), but there was not relationship between undernutrition and their development (p>0,05). The other factor that had relationship with their development were the achievement of D/S (p<0,05). Factors of nutritionist, midwife, intervention, TBC’s suspect, head of household education, mother education, member of family, children’s parity, social status, salary, scope of D/S, scope of N/D, and scope of vitamin A tablet supplementation did not have the relationship with the growth and development of children (p>0,05).Conclusion: There was relationship between previous undernutrition of children and their recent growth, but there was not with the recent development of children. The achievement of D/S was the other factor that had relationship with the growth of children.